Truth-Seekers Students' Critical Thinking Process in Solving Mathematics Problems with Contradiction Information - Ardiansyah, Kamal; Kurniati, Dian; Trapsilasiwi, Dinawati; Osman, Sharifah (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2022)
The aims of this study are (1) to describe the critical thinking processes of truth-seekers students in solving math problems with contradiction information based on the theory of mental mechanisms and structures, and (2) to find valid and effective learning models to improve the critical thinking processes of truth-seekers students. The subjects of this study were truth-seekers at SMPN 7 Jember. Data collection methods in this study were tests, observations, and interviews. The results of the research are that students who do truth-seeking in this study build mental mechanisms consisting of interiorization, coordination, and encapsulation and construct all mental structures, namely actions, processes, objects, and schemas. So, it can be concluded that the mental mechanism process of truth-seekers students in this study is not complete even though the mental structures have all been constructed in their minds. The model found to improve the critical thinking process based on the research findings is the infusion learning model by focusing on the habit of solving mathematical problems with contradiction information.Tujuan penelitian ini adalah (1) mendeskripsikan proses berpikir kritis siswa truth-seekers dalam menyelesaikan soal matematika dengan informasi yang kontradiksi berdasarkan teori mekanisme dan struktur mental, dan (2) menemukan model pembelajaran yang valid dan efektif untuk meningkatkan proses berpikir kritis siswa yang truth-seekers. Subjek penelitian ini adalah siswa yang truth-seekers di SMPN 7 Jember. Metode pengumpulan data pada penelitian ini adalah tes, observasi, dan wawancara. Hasil dari penelitian yaitu siswa yang melakukan truth-seeking dalam penelitian ini membangun mekanisme mental yang terdiri dari interiorisasi, koordinasi, dan enkapsulasi serta mengkonstruk seluruh struktur mental yaitu aksi, proses, objek, dan skema. Sehingga dapat disimpulkan bahwa proses mekanisme mental siswa truth-seekers dalam penelitian ini tidak lengkap walaupun struktur mentalnya telah dikonstruk semua dalam pikirannya. Model yang ditemukan untuk meningkatkan proses berpikir kritis berdasarkan temuan penelitian adalah model pembelajaran infusi dengan memfokuskan pada pembiasaan pemecahan masalah matematika dengan informasi yang kontadiksi.